THE POTENCY OF CAJUPUTS CANDY IN MAINTAINING THE COMPETITIVE CAPACITY OF STREPTOCOCCUS SANGUINIS UPON STREPTOCOCCUS MUTANS - Wijaya, Christofora Hanny; Sari, Bernadeta RE; Bachtiar, Boy M (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2020)
Streptococcus mutans were competing Streptococcus sanguinis in biofilm formation. As pioneer colonizer, S. sanguinis were able to control S. mutans growth. This study was aimed to explore the ability of sucrose and non-sucrose cajuputs candies (SCC and NSCC) in maintaining the antagonistic relationship between the indigenous oral flora when they grew as dual-species biofilms (S. sanguinis and S. mutans). The flavored candies (SCC and NSCC) contained cajuput and peppermint oils as the flavor which the volatile compounds had been identified. The unflavored candies were made similar to the flavored candy but excluding the flavor. The flavored candies, unflavored candies, and the control were exposed in vitro to the biofilms. The biofilms were examined for biofilm inhibition capacity, DNA amount, and the expression level of spxB mRNA. The biofilm inhibition by flavored candies were higher than the unflavored ones and were significantly different compared to the control. The flavored candies managed to decrease the total DNA amount in the biofilm, but unflavored samples did not. The qPCR assays showed that the exposure of candies did not alter the proportion of S. sanguinis DNA to S. mutans DNA in the biofilms. Meanwhile, spxB mRNA expression indicated the ability of S.sanguinis to control S. mutans growth.